Ants as indicators of disturbance at Yanchep National Park, Western Australia - Burbidge, A.; Leicester, K.; McDavitt, S.; Majer, Jonathan (1992)
Undisturbed sites at Yanchep National Park support ant communities which, in terms of species richness, evenness and functional group profiles, are typical of undisturbed sites elsewhere in south-western Australia. Slight modifications of the ecosystem result in slight alterations in ant communities. Replacement of native vegetation by gardens or plantations results in a considerable reduction in species and generic richness, reduction in the number of functional groups and altered species composition. Particular species of Crematogaster, Tapinoma and Iridomyrmex are indicative of relatively undisturbed sites, while particular species of Melophorus and Tetramorium are indicative of highly disturbed environments. Species richness of ants at undisturbed sites is not significantly correlated with numbers of vertebrate species at those sites.